How to justify propositions when facing skeptical challenges - Matías Pailós, Federico (Logos. Anales del Seminario de Metafísica, 2014)
Skeptical challenges question that the propositions one accepts are justified. But it is possible to justify each one of them in probabilistic terms. In order to do that, their probability, conditional to the rest of the accepted propositions, must be higher than their absolute probability. This justification is circular, but virtuous. Nevertheless, it has no dialectical efficiency against the skeptic.